(untitled) (Research, Society and Development, 2024)
The study deals with supernumerary teeth, which are extra teeth that can cause various complications in oral health, such as tooth crowding, impaction of permanent teeth and the formation of cysts. This article aims to review the literature on complications and treatments related to supernumerary teeth, focusing on extraction in a hospital environment, especially in pediatric patients. The research was carried out through an integrative literature review, using databases such as SciELO, PubMed and LILACS. Inclusion and exclusion criteria were established for the selection of articles, prioritizing those published between 2014 and 2024, with full and free access. After a careful search, 83 articles were found, of which 23 were selected for analysis, focusing on the clinical implications of supernumerary teeth in the general population. After analyzing the articles that refer to supernumerary teeth, it is clear the complexity and importance of an early and accurate diagnosis so that the treatment is adequate, avoiding future complications. The study concludes that the extraction of supernumerary teeth must be carried out carefully and planned, considering the particularities of each case. The approach in a hospital environment is recommended to ensure patient safety and comfort, especially in children, as well as the collaboration of a multidisciplinary team for effective treatment.